Cultural Competence and the Higher Education Sector 2020
DOI: 10.1007/978-981-15-5362-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Healing Mainstream Health: Building Understanding and Respect for Indigenous Knowledges

Abstract: We first encountered one another around a decade ago when sharing an office at a rural health campus of The University of Sydney, where both of us were working on health research projects. From that first meeting we were intuitively drawn to each other, and soon discovered shared interests, and some surprisingly common perspectives and opinions on health services, seen with an Indigenous Australian lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…We all yarned that our lessons from our professional practice and research have clearly shown that First Nations Peoples in Australia may choose to not seek healthcare because racism within healthcare services is experienced as being worse than their health challenges. This is discussed extensively through our own research and the work of others [ 9 , 20 , 58 , 59 , 60 , 61 ].…”
Section: Lessons From Yarning With a First Nations Health Researchermentioning
confidence: 99%
“…We all yarned that our lessons from our professional practice and research have clearly shown that First Nations Peoples in Australia may choose to not seek healthcare because racism within healthcare services is experienced as being worse than their health challenges. This is discussed extensively through our own research and the work of others [ 9 , 20 , 58 , 59 , 60 , 61 ].…”
Section: Lessons From Yarning With a First Nations Health Researchermentioning
confidence: 99%
“…As a result, terminology can become the focus for nurse educators, managers and those in positions of power within healthcare institutions. This is another barrier to understanding and teaching cultural safety (Rix & Rotumah, 2020b). Critical reflection and working in a person‐centred way with other cultures have been embedded within nursing curricula for decades (Burnard, 1988).…”
Section: Accomplices: Standing Alongside Indigenous Peoples In Their ...mentioning
confidence: 99%
“…We, however, ask: how can nurse education embrace cultural safety without a clear understanding of what it is, why it is so important and how to understand the pragmatics of owning safe practice? The majority of white nurse educators have a limited concept of what cultural safety really is, or the harm that their lack of knowledge, ongoing systemic bias and inherent power imbalances inflict on Indigenous students, patients and communities (Doran et al, 2019; Rix & Rotumah, 2020b). Mandating cultural safety/competence into undergraduate nursing and midwifery curricula is futile without ensuring the commitment of all non‐Indigenous academics to decolonise their own lenses and teaching (CATSINaM, 2020).…”
Section: Decolonising Nursing Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For Aboriginal and Torres Strait Islander peoples living with kidney disease and after transplantation, the health system must embed true partnership, engagement and, most importantly, real change from existing verbal feedback that is backed by evidence. Our health systems need to be empowered to embrace, accept and work with (and not against) Indigenous knowledges 7‐9 …”
mentioning
confidence: 99%